IMPLEMENTATION OF SUPPLY CHAIN MANAGEMENT IN IMPROVING CUSTOMER SATISFACTION (CASE STUDY AT PT SIDO MUNCUL TBK) - Fadilah, Sri; Mardiansyah, Dian; Rofiah, Azmiyati; Irmayati, Annisa (Yayasan Nuraini Ibrahim Mandiri, 2024)
The purpose of this research is to determine the implementation of Supply Chain Management (SCM) in improving customer satisfaction. Supply Chain Management is a management method that involves the integration of business processes among networks related to suppliers, manufacturers, distribution centers, and retailers. Customer satisfaction is the overall attitude shown by consumers towards goods and services after they have obtained and used them, and it represents the difference between what consumers expect and the situation provided by the company. The method used is a case study because the targeted company has already implemented Supply Chain Management in its operations. Data collection techniques include interviews and documentation. The results of this research prove that the proper implementation of Supply Chain Management by the company has an impact on customer satisfaction. Keywords: Supply Chain Management (SCM), Customer Satisfaction, Management Accounting, Production Management